2015
DOI: 10.1108/nlw-07-2014-0085
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and midwives’ information behaviour: a review of literature from 1998 to 2014

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:305060 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 60 publications
4
21
0
Order By: Relevance
“…This may not be a suitable focus to prepare graduates for the actual practices of the LPN workplace in which collaboration and teamwork in seeking and sharing information appear common. This result is also consistent with previous studies that have found nurses prefer to consult with colleagues when seeking information (Clarke et al., ; Ebenezer, ; O'Leary & Mhaolrúnaigh, ; Wahoush & Banfield, ). In addition, when asked to select in what areas more effective or increased training opportunities are needed, LPNs chose ‘Using information collaboratively in team‐based settings’ most frequently alongside ‘Developing lifelong learning skills through independent or social information‐seeking’.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may not be a suitable focus to prepare graduates for the actual practices of the LPN workplace in which collaboration and teamwork in seeking and sharing information appear common. This result is also consistent with previous studies that have found nurses prefer to consult with colleagues when seeking information (Clarke et al., ; Ebenezer, ; O'Leary & Mhaolrúnaigh, ; Wahoush & Banfield, ). In addition, when asked to select in what areas more effective or increased training opportunities are needed, LPNs chose ‘Using information collaboratively in team‐based settings’ most frequently alongside ‘Developing lifelong learning skills through independent or social information‐seeking’.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, it refers to information literacy skills and competencies as expressed in specific sociocultural frameworks (Fisher, Erdelez & McKechnie, , p. xix). Multiple studies have examined the information behaviour of nurses in the workplace (Clarke et al., ; Ebenezer, ; Ford & Korjonen, ). However, these tend to focus entirely on practitioners with baccalaureate‐level credentials or higher as opposed to graduates of two‐year programmes, who are referred to as registered practical nurses (RPNs) in Ontario and Licensed Practical Nurses (LPNs) in the rest of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, this finding supports evidence in the literature suggesting that health professionals often lack the confidence to search for and appraise health information [47][48][49]. This knowledge is important as it highlights the need to teach students studying to become health professionals the research skills required to locate and critically appraise the evidence, in order to become future evidence-based practitioners [50].…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies found that nurses with low levels of knowledge about scientific evidence recognise the benefits of using it in practice (Melnyk et al, ). However, they prefer human interactions, such as discussion with other clinicians, and experiential sources of knowledge, rather than reading scientific literature (Ebenezer, ). Many barriers can impede the search for evidence in clinical nurses, such as lack of time to read scientific articles, lack of familiarity with statistical terms and the exponential growth of published evidence (Brown, Wickline, Ecoff, & Glaser, ; Ebenezer, ; Majid et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they prefer human interactions, such as discussion with other clinicians, and experiential sources of knowledge, rather than reading scientific literature (Ebenezer, ). Many barriers can impede the search for evidence in clinical nurses, such as lack of time to read scientific articles, lack of familiarity with statistical terms and the exponential growth of published evidence (Brown, Wickline, Ecoff, & Glaser, ; Ebenezer, ; Majid et al, ). Results from this study show clinical expertise as a complementary and experiential source of knowledge that nurses with low level of scientific knowledge can easily access to support evidence‐based practice.…”
Section: Discussionmentioning
confidence: 99%